2008
DOI: 10.1016/j.psyneuen.2008.08.007
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between heart rate variability and inflammatory markers in cardiovascular diseases

Abstract: Summary Introduction Recent evidence implicates a cholinergic anti-inflammatory pathway. Because vagus nerve activity mediates some heart rate variability (HRV), this qualitative review examines the literature concerning circulating cytokines and HRV in cardiovascular function in humans. This qualitative review examines the literature concerning circulating cytokines and HRV in cardiovascular function in humans. Methods Thirteen studies on HRV, inflammation, and cardiovascular function were located by elect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
173
3
12

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 246 publications
(205 citation statements)
references
References 41 publications
8
173
3
12
Order By: Relevance
“…LF represents the sympathetic activity and HF indicates the parasympathetic activity [45,46]. The LF/HF values represent the balance condition between sympathetic and vagal tones [45,46]. The significantly enhanced LF and decreased HF in the MI rats suggest that myocardial ischemia has intensified the sympathetic activity.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…LF represents the sympathetic activity and HF indicates the parasympathetic activity [45,46]. The LF/HF values represent the balance condition between sympathetic and vagal tones [45,46]. The significantly enhanced LF and decreased HF in the MI rats suggest that myocardial ischemia has intensified the sympathetic activity.…”
Section: Discussionmentioning
confidence: 98%
“…HRV is a quantitative, noninvasive indicator of autonomic nervous function in the cardiovascular system [34,45,46]. LF represents the sympathetic activity and HF indicates the parasympathetic activity [45,46].…”
Section: Discussionmentioning
confidence: 99%
“…Exclusion criteria included a history or current diagnosis of any anxiety disorder and/or major depressive disorder and cardiovascular disease (hypertension, coronary artery disease, and arrhythmias) as these conditions are known to involve ANS dysfunction (Chalmers et al, 2014;Haensel et al, 2008;Kemp et al, 2012;Marano et al, 2009;Miu et al, 2009). Participants were excluded if they had a history of practicing mindfulness meditation or even minimal exposure to the practice (N60 min).…”
Section: Participantsmentioning
confidence: 99%
“…Insufficient parasympathetic function (corresponding with reduced HRV) can result in difficulties in reaching restful and relaxed states post-stress, while extended autonomic activity can accumulate as cardiovascular disease risks (Haensel et al, 2008;Kemp et al, 2012) and as stable or chronic anxiety-depressive conditions (Brosschot et al, 2006). Conversely, a growing literature associates increased HRV with enhanced attention-regulation (Chida and Steptoe, 2010;Segerstrom and Nes, 2007;Thayer et al, 2009) and with the practice of various forms of meditation (Burg and Wolf, 2012;Krygier et al, 2013;Phongsuphap et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The SAA level is sometimes increased in hyperglycemic subjects (11,12). Several prior studies have indicated a positive correlation between the HRs and C-reactive protein (CRP), another inflammatory marker (13,14). However, these studies did not focus on hyperglycemia, and there has been an observation that SAA is closer to CVD-related pathologies than other markers, such as CRP (15)(16)(17).…”
Section: Introductionmentioning
confidence: 99%